2010
DOI: 10.5194/angeo-28-907-2010
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen ion energization observed at high altitudes

Abstract: Abstract. We present a case study of significant heating (up to 8 keV) perpendicular to the geomagnetic field of outflowing oxygen ions at high altitude (12 R E ) above the polar cap. The shape of the distribution functions indicates that most of the heating occurs locally (within 0.2-0.4 R E in altitude). This is a clear example of local ion energization at much higher altitude than usually reported. In contrast to many events at lower altitudes, it is not likely that the locally observed wave fields can caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 28 publications
(34 reference statements)
3
24
0
Order By: Relevance
“…It is shown that mean wave intensities can explain the mean O + temperatures between 8 and 15 R E . In a case study of an enhanced perpendicular heating event at high altitude (12 R E ) made by Waara et al (2010) the high perpendicular temperature (8000 eV, which is about one order of magnitude higher than the mean temperature at the same altitude) could not be explained with simultaneous wave observations. If the heating is sporadic the chances to observe the heating when it actually takes place may be slim.…”
Section: Introductionmentioning
confidence: 91%
“…It is shown that mean wave intensities can explain the mean O + temperatures between 8 and 15 R E . In a case study of an enhanced perpendicular heating event at high altitude (12 R E ) made by Waara et al (2010) the high perpendicular temperature (8000 eV, which is about one order of magnitude higher than the mean temperature at the same altitude) could not be explained with simultaneous wave observations. If the heating is sporadic the chances to observe the heating when it actually takes place may be slim.…”
Section: Introductionmentioning
confidence: 91%
“…We want to find out if we typically can explain the observed ion temperatures with the simultaneously observed waves for each measurement point. If yes, then the result of Waara et al (2010) was clearly an exception and observed ion temperatures can in general be explained by simultaneously observed waves. If not, then the sporadic nature of the ion heating influences the statistics enough to lose a good correlation between ion temperature and wave activity.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent case study, Waara et al (2010) searched the high altitude cusp/mantle (the region of open magnetic field lines mapping to the polar cap and dominated by magnetosheath plasma) for the longest period with a significantly enhanced oxygen perpendicular to parallel temperature ratio, an expected sign of local transverse heating. They used the data set of Nilsson et al (2006) and found a case lasting about 20 min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barghouthi et al: A comparison study between observations and simulation results of Barghouthi model 2063 different regions may give discrepancies between our model results (which use fixed initial conditions) and observations. Regarding the observations of the ion velocity distribution functions, non-Maxwellian ion velocity distributions such as elevated conics and toroids have been reported in the different high-latitudes regions (Winningham and Burch, 1984;Huddleston et al, 2000;Waara et al, 2010;Slapak et al, 2011). Particle measurements performed onboard the Dynamics Explorer 1 (DE-1) satellite have revealed the existence of a population of O + ion conic extended in latitude throughout the equatorward portion of the auroral zone (Winningham and Burch, 1984).…”
Section: Introductionmentioning
confidence: 99%